Health system strengthening: a qualitative evaluation of implementation experience and lessons learned across five African countries - Felix Cyamatare Rwabukwisi; Ayaga A. Bawah; Sarah Gimbel; James F. Phillips; Wilbroad Mutale; Peter Drobac; the AHI PHIT Partnership Collaborative (BMC, 2017)
Abstract Background Achieving the United Nations Sustainable Development Goals in sub-Saharan Africa will require substantial improvements in the coverage and performance of primary health care delivery systems. Projects supported by the Doris Duke Charitable Foundation's (DDCF) African Health Initiative (AHI) created public-private-academic and community partnerships in five African countries to implement and evaluate district-level health system strengthening interventions. In this study, we captured common implementation experiences and lessons learned to understand core elements of successful health systems interventions. Methods We used qualitative data from key informant interviews and annual progress reports from the five Population Health Implementation and Training (PHIT) partnership projects funded through AHI in Ghana, Mozambique, Rwanda, Tanzania, and Zambia. Results Four major overarching lessons were highlighted. First, variety and inclusiveness of concerned key players (public, academic and private) are necessary to address complex health system issues at all levels. Second, a learning culture that promotes evidence creation and ability to efficiently adapt were key in order to meet changing contextual needs. Third, inclusion of strong implementation science tools and strategies allowed informed and measured learning processes and efficient dissemination of best practices. Fourth, five to seven years was the minimum time frame necessary to effectively implement complex health system strengthening interventions and generate the evidence base needed to advocate for sustainable change for the PHIT partnership projects. Conclusion The AHI experience has raised remaining, if not overlooked, challenges and potential solutions to address complex health systems strengthening intervention designs and implementation issues, while aiming to measurably accomplish sustainable positive change in dynamic, learning, and varied contexts.